Diabetic ketoacidosis complicated by chronic kidney disease in a domestic shorthair cat - Nur Atirah Suhaila Mohd Nordin; Sunita Krishnan (ARSHI Veterinary Letters, 2025)
Diabetic ketoacidosis (DKA) is a life-threatening metabolic complication secondary to diabetes mellitus (DM), a common endocrine disorder in cats. This condition is characterized by severe dehydration, electrolyte imbalance, and metabolic acidosis resulting from insulin deficiency and excessive ketone production. A 7-year-old castrated male cat presented with dyspnea, vomiting, marked dehydration, and hypothermia. Laboratory findings revealed severe hyperglycemia, glucosuria, ketonuria, azotemia, and elevated hepatic enzyme levels, confirming DKA complicated by chronic kidney disease. The cat received intensive therapy, including oxygen supplementation, intravenous fluids with potassium, insulin administration, antibiotics, and supportive care. Although transient improvement in electrolyte levels was achieved, glycemic control remained unstable, and the patient succumbed after three days of hospitalization.